Tamoxifen in the Mouse Brain: Implications for Fate-Mapping Studies Using the Tamoxifen-Inducible Cre-loxP System - Valny, Martin; Honsa, Pavel; Kirdajova, Denisa; Kamenik, Zdenek; Anderova, Miroslava (Frontiers in Cellular Neuroscience, 2016)
The tamoxifen-inducible Cre-loxP system is widely used to overcome gene targeting pre-adult lethality, to modify a specific cell population at desired time-points, and to visualize and trace cells in fate-mapping studies. In this study we focused on tamoxifen degradation kinetics, because for all genetic fate-mapping studies, the period during which tamoxifen or its metabolites remain active in the CNS, is essential. Additionally, we aimed to define the tamoxifen administration scheme, enabling the maximal recombination rate together with minimal animal mortality. The time window between tamoxifen injection and the beginning of experiments should be large enough to allow complete degradation of tamoxifen and its metabolites. Otherwise, these substances could promote an undesired recombination, leading to data misinterpretation. We defined the optimal time window, allowing the complete degradation of tamoxifen and its metabolites, such as 4-hydroxytamoxifen, N-desmethyltamoxifen, endoxifen and norendoxifen, in the mouse brain after intraperitoneal tamoxifen injection. We determined the biological activity of these substances in vitro, as well as a minimal effective concentration of the most potent metabolite 4-hydroxytamoxifen causing recombination in vivo. For this purpose, we analyzed the recombination rate in double transgenic Cspg4-cre/Esr1/ROSA26Sortm14(CAG-tdTomato) mice, in which tamoxifen administration triggers the expression of red fluorescent protein in NG2-expressing cells, and employed a liquid chromatography, coupled with mass spectrometry, to determine the concentration of studied substances in the brain. We determined the degradation kinetics of these substances, and revealed that this process is influenced by mouse strains, age of animals, dosage, and disruption of the blood-brain barrier. Our results revealed that tamoxifen and its metabolites were completely degraded within 8 days in young adult C57BL/6J mice, while the age-matched FVB male mice displayed more effective degradation. Moreover, aged C57BL/6J mice were unable to metabolize all substances within 8 days. The lowering of initial tamoxifen dose leads to a significantly faster degradation of all studied substances. A disruption of the blood-brain barrier caused no concentration changes of any tamoxifen metabolites in the ipsilateral hemisphere. Taken together, we showed that tamoxifen metabolism in mouse brains is age-, strain- and dose-dependent, and these factors should be taken into account in the experimental design.